Wave absorbing performance of polymer-derived SiCN(Fe) ceramics. Issue 17 (1st December 2017) - Wang, Youzhi; Guo, Xue; Feng, Yurun; Lin, Xiao; Gong, Hongyu
Abstract: Ferreous polymer-derived SiCN ceramics (PDCs-SiCN(Fe)) were successfully synthesized by precursor conversion method. The phase composition and microstructure of the obtained products were investigated by XRD, SEM and TEM. The result indicated a mainly amorphous structure with a few α-Fe, and graphite phases in the gaps. The conductivity, electromagnetic parameters and wave absorbing properties of the prepared ceramics were studied at the frequency band from 2 to 18 GHz. The reflectance of PDCs-SiCN(Fe) was about −10 dB (> 90% absorption) in the range of 4–16 GHz with 25 wt% nano-Fe2 O3 addition at the thickness 8 mm. The maximum value of dielectric and magnetic loss angle tangent was about 1.5, indicating PDCs-SiCN(Fe) ceramics possessed good absorption performance.